GIM-TEC adaptive ionospheric weather assessment and forecast system - Gulyaeva, T.L.; Arikan, F.; Hernandez-Pajares, M.; Stanislawska, I. (Journal of atmospheric and solar-terrestrial physics, 2013)
The Ionospheric Weather Assessment and Forecast (IWAF) system is a computer software package designed to assess and predict the world-wide representation of 3-D electron density profiles from the Global Ionospheric Maps of Total Electron Content (GIM-TEC). The unique system products include daily-hourly numerical global maps of the F2 layer critical frequency (foF2) and the peak height (hmF2) generated with the International Reference Ionosphere extended to the plasmasphere, IRI-Plas, upgraded by importing the daily-hourly GIM-TEC as a new model driving parameter. Since GIM-TEC maps are provided with 1- or 2-days latency, the global maps forecast for 1 day and 2 days ahead are derived using an harmonic analysis applied to the temporal changes of TEC, foF2 and hmF2 at 5112 grid points of a map encapsulated in IONEX format (−87.5°:2.5°:87.5°N in latitude, −180°:5°:180°E in longitude). The system provides online the ionospheric disturbance warnings in the global W-index map establishing categories of the ionospheric weather from the quiet state (W=±1) to intense storm (W=±4) according to the thresholds set for instant TEC perturbations regarding quiet reference median for the preceding 7 days. The accuracy of IWAF system predictions of TEC, foF2 and hmF2 maps is superior to the standard persistence model with prediction equal to the most recent ‘true’ map. The paper presents outcomes of the new service expressed by the global ionospheric foF2, hmF2 and W-index maps demonstrating the process of origin and propagation of positive and negative ionosphere disturbances in space and time and their forecast under different scenarios. •The Ionospheric Weather Assessment and Forecast, IWAF, system is developed.•IRI-Plas model is used to convert GIM-TEC into foF2 and hmF2 global IONEX maps.•GIM-TEC based W-index map specifies the ionosphere from quiet state to intense storm.•Fourier transform is applied for forecasting global maps 1 day and 2 days in advance.•Validation of IWAF system products is made with Topex/Jason and ionosonde data.